EFGR-mutant lung adenocarcinoma and Li-Fraumeni syndrome: Report of two cases and review of the literature. Issue 1 (January 2015) - Ricordel, Charles; Labalette-Tiercin, Marie; Lespagnol, Alexandra; Kerjouan, Mallorie; Dugast, Catherine; Mosser, Jean; Desrues, Benoit; Léna, Hervé
Highlights EGFR-mutated lung adenocarcinoma belongs to the spectrum of predisposed neoplasms in LFS. We provide the first description of resistance mutation to EGFR-TKI in a patient with LFS and lung adenocarcinoma. Response to targeted therapy may benefit to the same extent to LFS patient as in the general population.